Legal Arrangements on Waqf Money in the Context of Sharia Economics in Indonesia - H.M. Ridlwan Hambali; Anwar Saleh Hasibuan; Fathonah K. Daud; Farida Isroani; Muh. Abdulloh Hafith (Faculty of Law, Universitas Pekalongan, 2024)
Money waqf, a form of charitable giving in cash, is an emerging financial instrument in Indonesia's Islamic economy, complementing traditional in-kind wakaf such as land and buildings. While legal frameworks for its implementation exist through Law No. 41/2004 on Wakaf and Government Regulation No. 25/2018, challenges in its realization persist. These include limited public understanding of wakaf uang, influenced by the dominance of the Syafi'i school of thought, which traditionally focuses on immovable assets. Furthermore, insufficient socialization, institutional capacity, and government support hinder the effective mobilization of wakaf funds. Despite these challenges, the potential for wakaf uang to contribute to economic empowerment remains significant, especially with the rise of digital platforms facilitating easier participation. However, obstacles like low technological literacy and inadequate human resources within managing institutions need addressing. This research aims to evaluate the regulatory framework, challenges in implementation, and the role of wakaf uang in promoting socio-economic development in Indonesia. Findings emphasize the need for enhanced public education, stronger institutional management, and collaborative efforts between government, institutions, and the community to optimize the utilization of wakaf uang for greater economic impact.